Students' Perception Of Syariah Banking Study Program, Islamic University Of Negeri Mataram Towards Syariah Bank Services In Indonesia - minti, agus apriadi; Saadatirrohmi, Siti Ahdina; zulkifli, Zulkifli; Winata, Ari Trisna; Taqwa, Nuri Ahli (Universitas Islam Negeri Mataram, 2025)
This study is based on the facts about the services provided by Security , Customer Service and Tellerto customers. This type of research uses qualitative research methods, the data sources used areprimary data and secondary data. The data collection technique used by researchers usingparticipant observation, for the interview method the researcher used semi-structured interviewsand documentation. The data analysis technique used is the researcher using a descriptive analysismethod by exploring in depth how the informant's perception of the services provided by Security, Customer Service and Teller employees at Bank Syariah Indonesia. To check the validity of the data theresearcher used time triangulation. From the results of the study, different perceptions wereobtained from informants regarding the services provided by Security , Customer Service and Telleremployees at Bank Syariah Indonesia. Positive and negative perceptions were found from 20informants interviewed, in this study there were 12 informants whose perceptions were positiveand 8 informants whose perceptions were negative. Positive perceptions said that the servicesprovided by Security , Customer Service and Teller were very good, friendly and responsive in servingcustomers and did not like to discriminate between one customer and another. While negativeperceptions say that the services provided by Security , Customer Service and Teller are not good, notfriendly and not responsive in serving customers and like to differentiate between customers. Thisis influenced by experience, from what customers experience when making transactions at BankSyariah Indonesia KC Cakranegara. In addition, customer perceptions are obtained from theresults obtained after completing the use of the services that have been provided, whether theservice is carried out, customers will be more satisfied or not.